(untitled) (Research, Society and Development, 2021)
The growing demand for gluten-free foods, by people seeking more healthiness or who have dietary restrictions, has led to the acquisition of gluten-free foods. However, the development of gluten-free foods is a challenge due to the reduced nutritional value, requiring enrichment from other plant sources. A technological prospection study was carried out on the use of vegetables in the development of gluten-free food products, from October 10 to 18, 2020, by surveying technological information available in national and international patent databases, INPI and ESPACENET, respectively. Search strategies were defined using the association of keywords and international codes relevant to the topic. The results obtained in the international patent base differed by 490% in the period from 2001 to 2020, when compared with the national database. China stands out as a technology-dominated country, followed by the United States, Canada and Japan. Prospecting based on the number of patent filings revealed a 298% growth trend for gluten-free products, from 2001 to 2020, according to the international patent base, which emerges as an innovative alternative to meet the trends of the food market for the coming years.